(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Today availability of e-resourcesin a university library is very common. But their proper and maximum use is amatter for discussion. The present paper examines the existence of variouse-resource databases in Library and Information centre. The study alsohighlights the preferences and importance of online resources among theteachers and research scholars.